Effect of casing imperfection on the casing strength in steam injection wells - Hidayat, M.I.P. (Institute of Physics Publishing, 2017)
In this study, effect of casing imperfection on the casing strength in thermal environment of steam injection wells was investigated. The imperfections were modelled in the form of casing pits which may represent local cavitation, wear or corrosion attacks. Several pits with various depths (C) relative to the casing thickness (t) and different casing diameter to thickness (D/t) ratios were considered in this study. For the purpose of investigation, 3D FE models consisting of defective casing-cement-formation system were developed. N80 casing with the casing length of 3.048 m is analyzed in the numerical study. In the analysis, the combined effects of cyclic thermal stress (from 25 °C to 360 °C), collapse pressure (from formation) and defects on casing were taken into account. From the numerical study, it is found that the casing imperfection greatly affected the casing strength in steam injection wells. The presence of pits markedly reduces the casing collapse strength in comparison to that of non-defective casing. For instance, the collapse strength of casing having 2 pits along its circumferential direction with depth C = 0.5t reduced about 49 and 43 for D/t = 22.09 and D/t = 17.26, respectively. In addition, the combination of high temperature, imperfection factor and formation pressure induces severe deformation on casing, even at lower formation pressure. © Published under licence by IOP Publishing Ltd.